Additional grain boundary strengthening in length-scale architectured copper with ultrafine and coarse domains. (May 2019) - Hou, Xiaodong; Krauß, Sebastian; Merle, Benoit
Abstract: The strength of polycrystals is known to increase with decreasing grain size, known as Hall-Petch effect. However, this relationship fails to predict the strength of samples with a non-uniform distribution of grain sizes. In this study, we purposely designed and fabricated copper micropillars with a strongly bimodal microstructure: half volume consisted of a large number of ultrafine grains, while the other half was predominantly single-crystalline. Micropillar compression evidenced that bimodal samples are 35% stronger than their counterparts containing only ultrafine grains. This paradoxical finding highlights the greater strengthening potential of microstructure distribution engineering, compared to the traditional grain refinement strategy. Graphical abstract: Unlabelled Image